Education as Predictor of Low Birth Weight among Female Worker in Indonesia (Medico Legal Update, 2021)
Female workers are a vulnerable group in Indonesia because in addition to working to help their husbandsearn a living, they also still have to be responsible for domestic affairs. This study aimed to analyze the effectof the level of education on the incidence of LBW in female workers in Indonesia. The analysis uses the 2017Indonesian Demographic and Health Survey data. Stratification and multistage random sampling method get18,061 female workers as respondents. The final stage was done using binary logistic regression. The resultsfound that there was no difference between primary education female workers and no education femaleworkers at the risk of giving birth to LBW babies. Secondary education female workers have a 0.561 timeschance compared to no education female workers to give birth to LBW babies. Meanwhile, higher educationfemale workers have a possibility of 0.414 times compared to no education female workers to give birth toLBW babies. Apart from the education level, the results of the analysis also found two other variables aspredictors of LBW among female workers, namely wealth status and ANCvisits. It was concluded that theeducation level is a predictor of LBW among female workers in Indonesia. The higher the education level,the lower the possibility of female workers to have LBW babies in Indonesia.